2000
DOI: 10.1051/animres:2000138
|View full text |Cite
|
Sign up to set email alerts
|

Proposition d'une méthode subhumide de traitement des pailles à l'urée

Abstract: -Study of a subhumid method of straw processing with urea. We tested a subhumid processing method which reduces water content by 50% without the contribution of exogenous urease sources. The principle consisted in applying a 7% urea solution to one out of two layers of straw at a 40% humidity level, the last upper layer being systematically watered. The stack was then sealed as for classic ammoniation. At the same time, a classic treatment (also with 7% urea) was performed. At the end of the treatment which la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Some researchers (Mattoni et al, 2007;Larwence, 2000) have reported that urea supplementation increased DM and NDF contents in sorghum straw compared with the untreated straw. Silages with additives were lower than those without additives in hemicellulose and cellulose contents, and also b fraction of in situ rumen degradability for both DM and CP.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers (Mattoni et al, 2007;Larwence, 2000) have reported that urea supplementation increased DM and NDF contents in sorghum straw compared with the untreated straw. Silages with additives were lower than those without additives in hemicellulose and cellulose contents, and also b fraction of in situ rumen degradability for both DM and CP.…”
Section: Discussionmentioning
confidence: 99%
“…Cette augmentation est liée à la formation de produits (réaction de Maillard) non solubilisés, lors du dosage aux détergents neutres (Scheineider et Flachowsly, 1990). Une autre raison serait que des éléments solubles en présence d'une quantité importante d'eau soient solubilisés (Ben Salem et al, 2005a) et entraînés vers le fond lors du traitement (Larwence et al, 2000). Ce qui expliquerait l'augmentation plus importante des parois des gousses concassées.…”
Section: Effet De L'urée Sur La Composition Chimiqueunclassified